Viscoelastic response of an epoxy adhesive for construction since its early ages: Experiments and modelling - Silva, Patrícia (2017)
Epoxy adhesives have been extensively used in strengthening of reinforced concrete structures. In spite of that, research on the viscoelastic behaviour of these adhesives and its influence on the mechanical behaviour of strengthened concrete structures is scarce, particularly at the early ages of curing. The main goal of present work is to better understand the tensile creep behaviour of a specific commercial epoxy adhesive both at early ages and at long term. For this purpose, an experimental program comprising tensile creep tests was performed, in which epoxy specimens were subjected to: (i) equal stress levels but loaded at different ages, and; (ii) two different stress levels for a specific loading age. The results obtained have confirmed the viability of the principles of homogeneity and superposition, thus allowing the classification of this epoxy as linear viscoelastic. In addition, analytical simulations with Burgers model were carried out, and its predictive performance was considered insufficient at early ages, particularly upon unloading. In order to surpass some disadvantages of this model, a new framework is proposed to analytically evaluate the creep curing behaviour of this type of viscoelastic epoxy adhesives. The obtained results evidenced the capability of the proposed framework to predict the creep behaviour of an epoxy adhesive since its early ages.